Evaluasi Penyebab Tidak Berfungsinya Terminal Angkutan Umum di Ujong Fatihah Kabupaten Nagan Raya - Pardamean Pardamean; Irfan Irfan; Aulia Rahman (Jurnal Talenta Sipil, 2023)
The terminal is one of the components of the transportation system that  has the main function as a temporary stop for public vehicles to raise and distribute passengers and goods to the final destination of a trip, as well as a place to monitor, control, regulate, and operate the passenger and goods transportation flow system, besides that it also serves to facilitate the flow of transportation or goods.  The existence of the terminal in Ujong Fatihah that has been built by the government does not seem to be well used, and it does not look like it.  In the information obtained, this terminal is not used because there is no handover between the provincial government and the local government. This study aims to examine the causes of damage to the Ujong Fatihah terminal in Nagan Raya Regency using a descriptive method,  and examine the availability of Ujong Fatihah terminal facilities using  the weighting method. From the results  of  field  observations  and observations on the  Ujong Fatiha terminal facility, the causes of the malfunction of this terminal are: lack of availability of service facilities  such as safety, security, reliability, equality, comfort, and convenience.   The condition of the main  facilities and existing supporting facilities has been damaged.